2019
DOI: 10.5430/ijhe.v8n6p120
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Teachers’ Written Corrective Feedback as Perceived by EFL Teachers and Supervisors

Abstract: This study investigates EFL Post-Basic education teachers’ and EFL supervisors’ perceptions toward the importance of providing WCF and the practice of WCF including the techniques, focus, and follow-up methods. It attempts to examine the differences between teachers’ and supervisors’ perceptions on teachers’ WCF practices. The data was collected from 156 EFL teachers who were teaching Post-Basic education grades (11-12) and 62 EFL supervisors through using an online questionnaire. The two participant groups (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This result is consistent with the findings of Junqueira and Payant's (2015) study, in which participants believed in the importance of WF modes on errors related to organisation and content. In other studies (Al Kharusi & Al-Mekhlafi, 2019;Sakrak-Ekin & Balçikanli, 2019;Zaman et al, 2012), many of the respondents also agreed with the efficacy of WCF and perceived it as vital in developing students' writing. Similarly, Purnomo et al (2021) and Sakrak-Ekin and Zaman et al, 2012) also discovered that providing feedback on form, language use, content, organisation, and mechanics based on different WF modes appears to be crucial to teachers.…”
Section: Efl Instructors' Perceptions Of Product-and Process-based Wfmentioning
confidence: 69%
See 1 more Smart Citation
“…This result is consistent with the findings of Junqueira and Payant's (2015) study, in which participants believed in the importance of WF modes on errors related to organisation and content. In other studies (Al Kharusi & Al-Mekhlafi, 2019;Sakrak-Ekin & Balçikanli, 2019;Zaman et al, 2012), many of the respondents also agreed with the efficacy of WCF and perceived it as vital in developing students' writing. Similarly, Purnomo et al (2021) and Sakrak-Ekin and Zaman et al, 2012) also discovered that providing feedback on form, language use, content, organisation, and mechanics based on different WF modes appears to be crucial to teachers.…”
Section: Efl Instructors' Perceptions Of Product-and Process-based Wfmentioning
confidence: 69%
“…| Research ArticleBalçikanli (2019) found that most involved teachers viewed the provisions of WCF as valuable because they were easy to follow and understand. Other researchers (AlKharusi & Al-Mekhlafi, 2019;Alshahrani & Storch, 2014;Liu & Wu, 2019; …”
mentioning
confidence: 99%
“…The beliefs held by teachers regarding the significance of guiding students in enhancing their writing skills by identifying and rectifying any imperfections in their papers may shape the diverse feedback methodologies they employ (Kharusi & Al-Mekhlafi, 2019). As supported by Lee (2005), who draws upon his own research and other relevant studies, comprehending the underlying beliefs that drive teachers' instructional practices can aid in pinpointing the factors contributing to effective feedback.…”
Section: Teachers' Belief and Practices Of Written Corrective Feedbac...mentioning
confidence: 99%